Does different timing of hip and knee joint extension during take-off affect backstroke start performance? - Nara, R.; Ikeda, Y.; Shimojo, H.; Sato, D.; Ichikawa, H.; Baba, Y.; Shimoyama, Y. (Sports Biomechanics, 2021)
This study investigated how the difference in the timing of the extension of the joints of the lower limbs during take-off affects the backstroke start performance. Eleven backstroke swimmers performed three lower-limb joint extension sequences of backstroke start: knee extension after hip extension (KAH), simultaneous hip and knee extension (SHK), and knee extension before hip extension (KBH). The shortest 5-m time was performed at KAH (1.90±0.26 s), followed by a performance at SHK (2.12±0.52 s) and KBH (2.47±0.61 s). The greater trochanter (GT) vertical positions at toe-off were higher at KAH and SHK than at KBH. KAH had a shorter entry range, defined as the horizontal distance from the fingertip (FT) to the GT entry in the water, than KBH and SHK. A positive correlation was noted between the entry range and the 5-m time at KAH (r=0.79). In addition, a negative correlation was observed between the GT vertical position at toe-off and the entry range at KAH (r=-0.65). The results suggested that KAH makes it easier to take the arched-back posture after toe-off, allowing the performance of a hole-entry technique that reduces the entry range and the 5-m time.